Antenna array design and analysis - Ang, Bertrand Jun Jie (Nanyang Technological University, 2022)
With technology advancing and evolving quicker in the last century, long-distance communication has become an essential part of everyday life. Antennas are fundamental structure which has made wireless communication possible in modern society. Therefore, it is important for engineers who specialize in communications to gain more insight in how such structures work, along with its key principles. In this report, key concepts which are used in analyzing and designing an antenna and/or antenna array will be discussed. Topics such as the radiation pattern of dipole antennas, array factors and how the different parameters affect the output of the antenna and/or antenna array. By using the MATLAB software to show the different outputs of the antenna and/or antenna array, students will be able to visualize how the different parameters affect the outcome.